Serum Calprotectin Level as an Inflammatory Marker in Newly Diagnosed Hypertensive Patients - Nergiz Bayrakci; Gülsüm Ozkan; Sonat Pinar Kara; Ahsen Yilmaz; Savas Guzel (International Journal of Hypertension)
Background. Hypertension is one of the leading causes of cardiovascular mortality. Although the pathogenetic process involved is not yet fully understood, the disease involves endothelial damage and inflammation. Calprotectin is an inflammatory marker that rises in parallel with disease activity in conditions such as systemic inflammatory diseases, infection, and atherosclerosis. The purpose of this study was to evaluate inflammation through serum calprotectin levels in newly diagnosed primary hypertension patients. Methods. Forty-nine newly diagnosed hypertensive patients and 38 healthy adults were included in the study. Patients’ office blood pressure values, biochemical findings, and demographic characteristics were recorded. Serum calprotectin levels were measured using ELISA. Parameters affecting serum calprotectin levels and determinants of hypertension were evaluated. Results. Serum calprotectin levels were 242.8 (72.4–524) ng/mL in the control group and 112.6 (67.4–389.8) ng/mL in the hypertensive patient group, the difference being statistically significant (p=0.001). There was no correlation between serum calprotectin levels and other parameters (blood pressure values, age, gender, serum creatinine, uric acid, and calcium levels) in the hypertensive group. A lower serum calprotectin level was found to be independently related to hypertension (β = −0.009, p=0.005). Serum calprotectin at a cutoff level of 128.6 ng/mL differentiated hypertensives from healthy controls with a sensitivity of 69.4% and specificity of 68.4% (AUC = 0.767). Conclusions. The results of this study were the opposite of our hypothesis that a higher calprotectin level may reflect subclinical endothelial damage in newly diagnosed hypertensive patients. Further comparative studies involving patients at different stages of hypertension may contribute to clarifying the relationship between calprotectin and hypertension. We conclude that molecular studies seem essential for understanding the place of calprotectin in hypertension-associated inflammation, a complex process.